Production of oyster mushrooms (pleurotus florida and lentinus sajor-caju) at mushroom house, Faculty of Agriculture, UPM - Othman, Nur Asyiqin (2016)
Oyster mushrooms are edible mushrooms and are among the important cultivated mushrooms in the world. The growth and yield of these mushrooms are highly affected by temperature and humidity. This paper presents a study that was conducted on two different oyster mushrooms (Pleurotus florida and Lentinus sajor-caju) which was carried out in a mushroom house at the Department of Plant Protection, Faculty of Agriculture, Universiti Putra Malaysia from March to April. The objective of the experiment is to study the effect of temperature and humidity on the yield performance of oyster mushrooms. A total of 5 replications were used to cultivate each oyster mushroom. The temperature (°C) and humidity (%) of the mushroom house were measured by using a digital thermo-hygrometer daily. Pleurotus florida exhibited faster mycelial growth and primordial initiation compared to Lentinus sajor-caju in higher temperature and lower relative humidity. However, Lentinus sajor-caju showed higher yield and biological efficiency (BE%) compared to Pleurotus florida. Overall, temperatures and humidity affected the mycelial growth, primordial initiation and mushroom yields.